Relationship between online-learning self-efficacy and risk for psychological distress and harmful substance use in South African university students - Henning, Tiffany Joy (Department of Psychology, 2023)
The COVID-19 pandemic brought about rapid emergency changes in learning formats at universities globally, with a mass migration to online learning. Students' level of online learning self-efficacy (OLSE) may be an important determinant of how they cope with these changes. This study explored whether sociodemographic and online learning context factors are associated with OLSE among South African university students, whether OLSE predicts psychological distress and harmful substance use, and whether level of perceived social support moderates these relationships. It also examined whether psychological distress mediates the relationship between OLSE and problematic substance use. A cross-sectional online survey was administered to students from the University of Cape Town (n = 627). Students who had higher levels of access to online learning resources, and students who were white had higher levels of OLSE, while students on a government bursary and those living in university residences rather than with family members had lower OLSE. Lower OLSE was found to be a significant predictor of higher psychological distress and increased harmful substance use, when controlling for sociodemographic and online learning context factors. Psychological distress mediated the relationships between OLSE and harmful alcohol and marijuana use. Perceived social support did not moderate the relationships between OLSE and mental health difficulties or substance use. These findings indicate that OLSE is an important predictor of how university students cope with online learning demands and suggest that students with lower OLSE should be identified and better supported with strategies to improve their OLSE levels. Further, students with lower OLSE levels may need greater mental health support from universities within the context of online learning, as the existing social supports do not appear to be adequately protective for students.